Peningkatan Kemampuan Berbicara Siswa kelas XII SMA Negeri 1 Waipia Kecamatan TNS Melalui Metode Debat - Weldemina Serpara; Henderika Serpara (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2021)
The purpose of this study is to improve and improve the quality of learning German, especially good ways of speaking in German, and to help empower teachers in solving classroom teaching problems. This research is classroom action research. The subjects of this classroom action research were students of class XII SMA Negeri 1 Waipia, TNS District. Learning Development and Innovation are detailed starting with development planning, development implementation, and observation, as well as cyclic reflection. This classroom action research was conducted in 2 (two) cycles. . The results of this study indicate that there is an increase in students' German-speaking skills through the Debate method. This is proven that in the first cycle there were 4 students or 21.05% who got low scores, 13 students or 68.42% who got moderate grades, and 2 students or 25% who got good grades from the 19 students who were sampled. Meanwhile, there were 12 students (63.16%) who got moderate grades and 7 students (36.84%) who got good grades from the 19 students who were sampled. Based on the results obtained in cycle II it turns out that 19 students or 100% are at the level of completeness, thus it can be considered that this Debate method can be said to be successful in improving students' speaking skills